Early processes in heme-based CO-sensing proteins - Vos, Marten H.; Salman, Mayla; Liebl, Ursula (Frontiers in Molecular Biosciences, 2022)
Carbon monoxide has been recognized relatively recently as signaling molecule, and only very few dedicated natural CO sensor proteins have been identified so far. These include in particular heme-based transcription factors: the bacterial sensor proteins CooA and RcoM. In these 6-coordinated systems, exchange between an internal protein residue and CO as a heme ligand in the sensor domain affects the properties of the DNA-binding domain. Using light to dissociate heme-ligand bonds can in principle initiate this switching process. We review the efforts to use this method to investigate early processes in ligand switching and signaling, with an emphasis on the CO-‘trapping’ properties of the heme cavity. These features are unusual for most heme proteins, but common for heme-based CO sensors.